Home-Based Orolingual Exercise Improves the Coordination of Swallowing and Respiration in Early Parkinson Disease: A Quasi-Experimental Before-and-After Exercise Program Study - Wang, Chin-Man; Shieh, Wann-Yun; Ho, Chan-Shien; Hu, Yu-Wei; Wu, Yih-Ru (Frontiers in Neurology, 2018)
Introduction: The coordination of swallowing and respiration is important for safety swallowing without aspiration. This coordination was affected in Parkinson disease (PD). A noninvasive assessment tool was used to investigate the effect of an easy-to-perform and device-free home-based orolingual exercise (OLE) program on swallowing and respiration coordination in patients with early-stage PD. Materials and Methods: This study had a quasi-experimental before-and-after exercise program design. Twenty six patients with early-stage PD who were aged 62.12 ± 8.52 years completed a 12-week home-based OLE program. A noninvasive assessment tool was used to evaluate swallowing and respiration. For each patient, we recorded and analyzed 15 swallows (3 repeats of 5 water boluses: 1, 3, 5, 10, and 20 mL) before and after the home-based OLE program. Oropharyngeal swallowing and its coordination with respiration were the outcome measures. The frequency of piecemeal deglutition, pre- and post-swallowing respiratory phase patterns, and parameters of oropharyngeal swallowing and respiratory signals (swallowing respiratory pause [SRP], onset latency [OL], total excursion time [TET], excursion time [ET], second deflexion, amplitude and duration of submental sEMG activity, and amplitude of laryngeal excursion) were examined. Results: The rate of piecemeal deglutition decreased significantly when swallowing 10- and 20-mL water boluses after the program. In the 1-mL water bolus swallowing trial, the rate of protective pre- and post-swallowing respiratory phase patterns was significantly higher after the program. For the parameters of oropharyngeal swallowing and respiratory signals, only the amplitude of laryngeal excursion was significantly lower after the program. Moreover, the volume of the water bolus significantly affected the SRP and duration of submental sEMG when patients swallowed three small water bolus volumes (1, 3, and 5 mL). Conclusion: The home-based OLE program improved swallowing and its coordination with respiration in patients with early-stage PD, as revealed using a noninvasive method. This OLE program can serve as a home-based program to improve swallowing and respiration coordination in patients with early-stage PD.